2019
DOI: 10.1111/dom.13810
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic control in individuals with type 1 diabetes using an open source artificial pancreas system (OpenAPS)

Abstract: Open source artificial pancreas systems (OpenAPS) have gained considerable interest in the diabetes community. We analyzed continuous glucose monitoring (CGM) records of 80 OpenAPS users with type 1 diabetes (T1D). A total of 19 495 days (53.4 years) of CGM records were available. Mean glucose was 7.6 ± 1.1 mmol/L, time in range 3.9–10 mmol/L was 77.5 ± 10.5%, <3.9 mmol/L was 4.3 ± 3.6%, <3.0 mmol/L was 1.3 ± 1.9%, >10 mmol/L was 18.2 ± 11.0% and > 13.9 mmol/L was 4.1 ± 4.0%, respectively. In 34 OpenAPS users,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 6 publications
9
66
0
2
Order By: Relevance
“…This is in line with previous studies evaluating DIYAPS. [10][11][12][14][15][16][17][18] Our findings collectively underpin the robustness of DIYAPS as a seemingly effective approach among T1D patients irrespective of baseline HbA1c.…”
Section: Discussionsupporting
confidence: 53%
“…This is in line with previous studies evaluating DIYAPS. [10][11][12][14][15][16][17][18] Our findings collectively underpin the robustness of DIYAPS as a seemingly effective approach among T1D patients irrespective of baseline HbA1c.…”
Section: Discussionsupporting
confidence: 53%
“…In consonance with these findings, a UK observational study concluded that OpenAPS initiation The authors also observed that a change from sensor-augmented pump (SAP) therapy to OpenAPS in 34 of the users significantly reduced the mean glucose, estimated HbA1c, time in hypo and hyperglycemia, and accretion in TIR. In short, this study conclusively proved that OpenAPS systems are as competent as the other meticulously developed and tested devices [31,32]. Koutsovasilis et al reported that the use of OpenAPS systems in patients with T1D (n = 24) resulted in appreciable glycemic control in terms of HbA1c, fasting blood glucose (FBG), pre-meal, post-meal, and before bedtime glucose, less or no hypoglycemic events, and reduction in daily BG fluctuations [33].…”
Section: Current Literature On Diyapssupporting
confidence: 55%
“…You must give patients the information they want or need about… c. options for treating or managing the condition… f. whether a proposed investigation or treatment is part of a research programme or is an innovative treatment designed specifically for their benefit… l. any treatments that you believe have greater potential benefit for the patient than those you or your organisation can offer. [15] Although not provided directly by the doctor or the National Health Service (NHS), DIY APS are precisely 'an innovative treatment designed specifically for their benefit', and based on observational data [16,17], a treatment that offers 'greater potential benefit for the patient'. Taking these two points together, it could thus be argued that doctors should discuss DIY APS with people living with type 1 diabetes.…”
Section: Ethics Of the Diy Artificial Pancreas For The Professionalmentioning
confidence: 99%